PENGAMBILAN KEPUTUSAN DALAM BERINVESTASI DI PASAR MODAL - Nurul Nadia Tasa nadia; Restia Melinda; Syintia Efendi (Jurnal Mahasiswa Akuntansi Samudra, 2022)
Investment decision making is a process that includes several factors and follows various steps. The purpose of this study is to find out what are the factors that a person considers in deciding to invest in the capital market. The four factors a person decides to invest in the capital market are investment interest, perception of investment, investment motivation, and initial investment capital. This study can provide information, especially for novice investors to be able to make decisions to invest in the capital market. The research method used is a qualitative method